Exploring the physiological efficiencies of promising rice (Oryza sativa) accessions for increasing grain yield - PANDA, BABYRANI; DASH, SUSHANTA K; MONDAL, SUBHANKAR; SENAPATY, JEETENDRA; DASH, MANASI; SAMAL, KAILASH C; SAHOO, CHITTA R; CHAKRABORTY, KOUSHIK (The Indian Journal of Agricultural Sciences, 2023)
High grain yield in rice (Oryza sativa L.) is a cumulative contribution of different morphological and physiological traits. However, the selection of high-yielding genotypes based on physiological traits is difficult where a large set of genotypes is used. Therefore, a study was carried out during rainy (kharif) seasons of 2019 and 2020 at research farm of ICAR-National Rice Research Institute, Cuttack, Odisha to assess the physiological efficiency of 211 elite rice genotypes having varying yield potential. The elite genotypes were classified into high, medium, and low categories based on their field performance. The results revealed that 29, 41, 34, 31, 49, 35, 39, 29, and 30 genotypes showing high values for FLA (>51.51 cm2), TCC (>3.99 mg/g fresh weight), PN (>20.79), gs (>0.97), E (>9.03), TB (>15.95 t/ ha), GY (>6.27 t/ha), PR (>0.29 kg/cm), and CS (>42.12 g/stem) respectively. Among them, 3 genotypes i.e. IG-020, IG-211 and IG-010 were identified to be highly efficient in 4 traits, 2 genotypes i.e., IG-044 and IG-186 in 5 traits, and 2 genotypes; IG-008 and IG-161 were found to be superior in 7 traits along with high grain yield. The selection of these genotypes with superior morphological and physiological traits could be beneficial in the breeding programme in terms of increasing yield potential in rice.